Hall and Thermo‐Diffusion Effects on Chemically Reactive MHD Unsteady Brinkman‐Type Dissipative Flow of EO‐Based MoS2 Nanofluid From a Rotating Plate in Porous Medium - B. Prabhakar Reddy; Jumanne Mng'ang'a; M. Paul Matao (Engineering Reports)
ABSTRACT In many mechanical systems, the friction is a major aspect in the energy loss. However, lubrication is the ultimate way to reduce friction. The engine‐oil is the prominent lubricant for internal combustion engines. Last few decades, nanofluids gained credit as an inventive low‐friction technology that significantly lowers emissions and keeps great energy savings. Therefore, this study analyzes the thermo‐diffusion Brinkman‐type radiative engine‐oil based unsteady magnetohydrodynamics heat consuming Molybdenum‐disulfide nanofluid flow with Hall, chemical reaction and viscous dissipation impacts from a rotating plate in porous environs. The finite difference numerical scheme was utilized to get the numerical solutions of the flow fields. The numerical results accomplished for velocity, temperature and concentration relating to assorted flow parameters with the help of MATLAB are interpreted graphically whilst the engineering quantities by tables. The ultimate results bring‐out that the temperature and both velocity components upsurges due to viscous dissipation and radiation effects but heat consumption affects oppositely. The nanoparticle's volume fraction significantly improves the temperature field. The Brinkman parameter and nanoparticle's volume fraction causes to slow‐down both velocity components whereas thermo‐diffusion and Hall parameters have exposed opposite impact. The magnetic field and rotational parameters tend to downgrade the primary velocity and heightens the secondary velocity. The concentration field repressed by the chemical reaction reagent. Heat transfer rate enhanced at the surface by increasing viscous dissipation and volume fraction but it is lessened with radiation and heat‐consumption. Interestingly, the heat transfer rate significantly raises to 3.97% when dispersing 4% Molybdenum‐disulfide nanoparticles to engine‐oil which enhanced its lubrication.